C-Band Q-Switched Fiber Laser Using Titanium Dioxide (TiO 2) As Saturable Absorber - H. Ahmad; Siti Aisyah Reduan; Zainal Abidin Ali; M. A. Ismail; N. E. Ruslan; C. S. J. Lee; R. Puteh; S. W. Harun (IEEE Photonics Journal)
We demonstrate a passively Q-switched erbium fiber laser using titanium dioxide (TiO 2) as a saturable absorber. The TiO 2 saturable absorber was fabricated as a polymer composite film and sandwiched between fiber ferrules. Q-switched pulsing starts with the assistance of physical disturbance of the laser cavity (by lightly tapping the cavity to induce instability) at 140 mW and lasts until 240 mW. The repetition rate increases with the pump power from 80.28 to 120.48 kHz. On the other hand, the pulsewidth decreases from $2.054\ μ\text{s}$ until it reaches a plateau at $1.84\ μ\text{s}$ . The Q-switched fiber laser exhibits two competing modes: at 1558.1 and 1558.9 nm as the pump power increases. A high signal-to-noise ratio of 49.65 dB is obtained.